Preventive influence of regular physical exercise on the incidence of common cold - a literature review - Adam Czarnecki; Aleksandra Nosal; Aleksandra Galanty-Ochyra; Piotr Zając; Jan Węgrzyn; Łukasz Fijałkowski; Karolina Serwońska; Artur Pastuszka; Olga Jabłońska (Journal of Education, Health and Sport)
Introduction and purpose: